Sistem Informasi Web Profile Pada Program Studi Peternakan Universitas Pembangunan Panca Budi Medan - Ade Rizka; Ariyati Peranita; Imelia Octaviani (Indonesian Journal of Education And Computer Science, 2023)
An important information system to help distribute information to users who have access in real time. The use of the system can help institutions to introduce institutional profiles. The information system for the Animal Husbandry study program has not been built independently, so there are obstacles in distributing information to users or the public. An institutional web profile system specifically for the Animal Husbandry study program is needed in order to increase the interest and trust of community users to join the Animal Husbandry study program and institutional users get regular information. The system is designed and built using the waterfall method. The Animal Husbandry study program web profile system is designed using the UML model. The system was successfully built independently to introduce an institutional profile specifically for the Animal Husbandry study program. With an independent system, it helps to distribute directly validated Animal Husbandry study program information. Study programs can also maximize the system to improve performance and quality. The system is implemented for users and system testing is carried out using a black box, all interfaces that have been tested with 6 activities, namely having no problems or in accordance with current user needs